Wykorzystanie kryterium Kołmogorowa-Smirnowa przy budowie drzewa klasyfikacyjnego dla zbioru obiektów symbolicznych - Gliwa, Małgorzata (Using of the Kolmogorov-Smirnоv Criterion While Building Classification Tree for Set of Symbolic Objects, 2007)
If we are interested in dividing symbolic objects' into groups, as regards to specific variable values, it would be more comfortable to present this process as a decision tree. To build decision tree, we need a criterion in order to split the symbolic objects' set in a nodes. In this article the Kolmogorov-Smimov criterion is presented, as a splitting criterion of symbolic objects' set. For this criterion, the values taken by the explanatory variables have to be ordered. We considered different possible orders of interval and histogram variables. At the end we show an example to illustrate this approach.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 160-168